2016
DOI: 10.2522/ptj.2016.96.7.e1
|View full text |Cite
|
Sign up to set email alerts
|

The Single-Case Reporting Guideline In BEhavioural Interventions (SCRIBE) 2016 Statement

Abstract: Reporting guidelines, such as the Consolidated Standards of Reporting Trials (CONSORT) Statement, improve the reporting of research in the medical literature (Turner et al., 2012). Many such guidelines exist and the CONSORT Extension to Nonpharmacological Trials (Boutron et al., 2008) provides suitable guidance for reporting between-groups intervention studies in the behavioral sciences. The CONSORT Extension for N-of-1 Trials (CENT 2015) was developed for multiple crossover trials with single individuals in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(90 citation statements)
references
References 29 publications
0
88
0
2
Order By: Relevance
“…Disagreements between the reviewers were resolved by discussion with a third reviewer (AG). As regards within-subject designs, the Single-Case Reporting Guideline In Behavioural Interventions (SCRIBE) Statement (Tate et al, 2016a , b ) was followed. As regards pre-post designs, a Quality Assessment Tool adapted from several published systematic reviews (see Cummings et al, 2008 ) was adopted.…”
Section: Resultsmentioning
confidence: 99%
“…Disagreements between the reviewers were resolved by discussion with a third reviewer (AG). As regards within-subject designs, the Single-Case Reporting Guideline In Behavioural Interventions (SCRIBE) Statement (Tate et al, 2016a , b ) was followed. As regards pre-post designs, a Quality Assessment Tool adapted from several published systematic reviews (see Cummings et al, 2008 ) was adopted.…”
Section: Resultsmentioning
confidence: 99%
“…Single-case experimental design (SCED) was utilized to conduct this study; methods and results are reported in accordance with single-case reporting guideline in behavioral interventions (SCRIBE; Tate et al, 2016). This type of design is particularly helpful for preliminary studies with small sample sizes, as a means to gather evidence in support of novel treatment strategies (Kazdin, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…As such, SCEDs are capable of establishing robust causal relationships and may provide high levels of evidence (for an overview and historical context see Vlaeyen et al, 2020). While the strengths of such designs are reflected in the growing interest (Hammond and Gast, 2010) and the development of guidelines (Tate et al, 2016), this methodology is still under-explored in the tinnitus field. The idiosyncratic nature of tinnitus provides a rich soil where SCED may thrive by providing robust and individualized baselines to which treatment effects are compared.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%